2017
DOI: 10.14738/tmlai.54.3210
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Undergraduate Students’ Attitudes Towards English Mobile Learning

Abstract: The increase of mobile devices, the availability of several features, and the decrease in terms of cost of smartphones made them useful not only for communication, but also for learning. Similarly, the importance of English in higher education makes it one of the most fundamental foreign languages that students want to learn. Many students look for different ways to learn English. Among these ways is Mobile Learning which becomes nowadays a useful tool for language learning due to the evolution of mobile techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Hulstijn (2001) also advocated that students can use their smart phones for learning new vocabulary using electronic dictionary. The findings of this study are parallel with what was previously found by Omari, Bourekkadi, Slimani, Khoulji and Kerkeb (2017) who stated that most Moroccan students affirmed that they applied their mobile phones mainly to listen to songs. Similar results in another study by Chhikara (2015) also demonstrated that using mobile phones in learning English among Indian learners was very helpful because it assisted them to improve and develop the skills of reading, writing, speaking and listening.…”
Section: Discussionsupporting
confidence: 90%
“…Hulstijn (2001) also advocated that students can use their smart phones for learning new vocabulary using electronic dictionary. The findings of this study are parallel with what was previously found by Omari, Bourekkadi, Slimani, Khoulji and Kerkeb (2017) who stated that most Moroccan students affirmed that they applied their mobile phones mainly to listen to songs. Similar results in another study by Chhikara (2015) also demonstrated that using mobile phones in learning English among Indian learners was very helpful because it assisted them to improve and develop the skills of reading, writing, speaking and listening.…”
Section: Discussionsupporting
confidence: 90%
“…Evaluating the differences in terms of motivation between public and private universities in Morocco will add to the literature that looks at this comparison. Moreover, nowadays there is a big shift to English mobile learning, and Moroccan university students demonstrated nowadays that they have positive attitudes toward English mobile learning (Omari, Bourekkadi, Slimani, Khoulji, & Kerkeb, 2017). In fact, Studies on students' motivation will be of great use to language teachers and also to textbooks and mobile apps designers because they will be provided with research evidence.…”
Section: Introductionmentioning
confidence: 99%